2014
DOI: 10.1021/ja502646c
|View full text |Cite
|
Sign up to set email alerts
|

Active Sites and Mechanisms for Oxygen Reduction Reaction on Nitrogen-Doped Carbon Alloy Catalysts: Stone–Wales Defect and Curvature Effect

Abstract: Carbon alloy catalysts (CACs) are promising oxygen reduction reaction (ORR) catalysts to substitute platinum. However, despite extensive studies on CACs, the reaction sites and mechanisms for ORR are still in controversy. Herein, we present rather general consideration on possible ORR mechanisms for various structures in nitrogen doped CACs based on the first-principles calculations. Our study indicates that only a particular structure of a nitrogen pair doped Stone-Wales defect provides a good active site. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
247
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(264 citation statements)
references
References 67 publications
8
247
0
4
Order By: Relevance
“…It was shown recently that modification of the nonmetal heteroatom doped carbon with transition metal species could promote its ORR activity to a level comparable to that of Pt‐based catalyst 17, 18, 19, 20, 21. Although the detailed mechanism for this performance enhancement is not clearly understood yet,22, 23 these results clearly outlined the potential of the metal and nonmetal heteroatom codoped carbon for the development of high performance and low cost ORR catalyst.…”
mentioning
confidence: 82%
“…It was shown recently that modification of the nonmetal heteroatom doped carbon with transition metal species could promote its ORR activity to a level comparable to that of Pt‐based catalyst 17, 18, 19, 20, 21. Although the detailed mechanism for this performance enhancement is not clearly understood yet,22, 23 these results clearly outlined the potential of the metal and nonmetal heteroatom codoped carbon for the development of high performance and low cost ORR catalyst.…”
mentioning
confidence: 82%
“…These defects can also locally induce Gaussian curvatures to alter bond lengths and rehybridize electron orbitals [114], leading to electron redistribution and therefore high ORR activities [115]. In addition, the ORR performance of N-doped graphene can also be greatly enhanced by Stone-Wales defects, which decrease the HOMO-LUMO energy gap of nanoscale graphene domains and change reaction pathways [116,117].…”
Section: Defect-induced Charge Transfermentioning
confidence: 99%
“…Line defects (e.g., edges, cracks, voids [113]) in graphene sheets were revealed to be also efficient for electrochemical 1 3 catalysis (e.g., ORR) [116]. On the edge side, localized states are induced along the edge length to modify local band structures and change the electron properties of the nanocarbon.…”
Section: Defect-induced Charge Transfermentioning
confidence: 99%
“…The influence of dopants on graphene surfaces with defects has been investigated by quantum chemical approaches 202,[207][208][209][210][211] . In one recent report 210 a large part of their work was devoted to an exhaustive study of boron, nitrogen, and B/N co-dopants on the double-vacancy (555-777) graphene surface.…”
Section: Fuel Cellsmentioning
confidence: 99%
“…Their periodic PBE calculations (based on both an infinite graphene plane and a (10,0) carbon nanotube) indicated that O 2 adsorption strength over the Si dopant site increased when going from a convex, to flat, to a concave surface, with the corresponding free energy change of the rate-determining step in the ORR becoming lower. Tuning of the ORR catalytic activity via manipulation of interfacial curvature was also the subject of a quantum chemical study reported by Chai et al 211 , who considered nitrogen dopants in graphene sheets (both basal sites and edge sites) and (n,0) carbon nanotubes (where n =6-18). These authors also considered the presence of defects (mainly divacancy and Stone-Wales defects) in these doped structures.…”
Section: Fuel Cellsmentioning
confidence: 99%